On-tissue Direct Monitoring of Global Hydrogen/Deuterium Exchange by MALDI Mass Spectrometry: Tissue Deuterium Exchange Mass Spectrometry (TDXMS) - Quanico, Jusal (Mol Cell Proteomics, 2016)
Hydrogen/deuterium exchange mass spectrometric (H/DXMS) methods for protein structural analysis are conventionally performed in solution. We present Tissue Deuterium Exchange Mass Spectrometry (TDXMS), a method to directly monitor deuterium uptake on tissue, as a means to better approximate the deuterium exchange behavior of proteins in their native microenvironment. Using this method, a difference in deuterium uptake behavior was observed when the same proteins were monitored in solution and on tissue. The higher maximum deuterium uptake at equilibrium for all proteins analyzed in solution suggests a more open conformation in the absence of interacting partners normally observed on tissue. We also demonstrate a difference in the deuterium uptake behavior of a few proteins across different morphological regions of the same tissue section. Modifications of the total number of hydrogens exchanged, as well as the kinetics of exchange, were both observed. These results provide information on the implication of protein interactions with partners as well as on the conformational changes related to these interactions, and illustrate the importance of examining protein deuterium exchange behavior in the presence of its specific microenvironment directly at the level of tissues.